How would you differentiate f(x)=3x(2x-1)^2

This question is really straight forward

By using the Chain rule: f'(x) = uv' + u'v.

let u=3x, so u'=3

let v=(2x-1)^2, so v'=2x2(2x-1)=8x-4

Now, we put this expression altogether:

As f'(x) = uv' + u'v

f'(x)=3x(8x-4)+3(2x-1)^2

f'(x)=24x^2-12x+12x^2+3-12x

And now, simplify

f'(x)=36x^2-24x+3

Answered by Ruihang Z. Maths tutor

5630 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Can I have help with integrating by parts? I am unsure on how to use the formula.


When do you know to use integration by parts?


The curve C has the equation: 2(x^2)y + 2x + 4y – cos (πy) = 17 use implicit differentiation to find dy/dx in terms of x and y


Integrate the function y = 2x^2 + 3x + 8 with respect to x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences